Gamearte: subversão e diversão na arte contemporânea - Witt, Anelise Vieira dos Santos (2013)
The target of this research is to help the thinking about contemporary art through a new approach from the Idea of play to gaming. We try to comprehend the overthrow and entertainment concepts in the games developed and in the art and gaming field. This observation doesn‟t lay down just on the games created in this research, but also include a few aspects of art and technology in contemporary art. Between practice and theory the methodology was built, and together they tangled the proposed thought. To elucidade the thought tha we came with in this study we start with the approach of the play concept, that raises on philosophy and is adopted by the visual arts. From philosophycal play to eletronic game, and when it is found on a artistic context, it can be called as art and gamimg. In trying to understand and define what exactly art and gaming are about I show my own artistic games. This master thesis ends with a view of the contemporary art scenery and how the overthrow and entertainment concepts can integrate the contemporary art today.